The Facts Still There is Legal Discrimination in Indonesia - Devina Arifani; Siti Sa'atun; Armunanto Armunanto (LAW FACULTY UNISSULA, 2022)
Justice is a desire that must be fulfilled in enforcing the law. Justice has an individualistic nature and does not generalize. If law enforcers hold fast to the value of justice but the value of usefulness and legal certainty is not considered, then the law will not run smoothly. Then if you focus on the value of expediency but neglecting legal certainty and justice, the law will not work. If you want to enforce the law, the values of justice, benefits and legal certainty must be balanced and in harmony. The law can be enforced if it has credible, competent and independent law enforcement officers. As good as a law is, if it is not supported by good law enforcement officers, justice will not be created. The powers of law enforcement agencies are regulated by law. So in carrying out their duties and responsibilities, they are not affected by government authority or outside influences. The crucial problem in law enforcement is not only against uncooperative legal products but also because the law enforcement officers still carry out glaring discrimination, namely the difference in the handling of cases between the poor and the rich/ranking. Therefore, the saying